The Chris Farley show : a biography in three acts - Farley, Tom, 1961-; Colby, Tanner (New York : Penguin Books, 2009)
Traces the late comedian's passionate dedication to bringing laughter into the lives of others, his successes on'Saturday Night Live' and in numerous top films, and the incapacity for moderation that led to his fatal battle with drugs and alcohol.
Includes filmographies (pages : 337-342) and index.
Keywords: Farley, Chris, -- 1964-1997.; Comedians -- United States -- Biography; Actors -- United States -- Biography